Associations Between Cognitive Function, Depression, and Olfactory Function in Elderly People With Dementia in Korea - Cha, Hyegyeong; Kim, Sisook; Son, Yedong (Frontiers in Aging Neuroscience, 2022)
Elderly dementia patients have been increasing rapidly. Also, olfactory function and depression is common in dementia patients. Thus, this study aimed to investigate the influence of each domain of cognitive function and depression on olfactory function among elderly dementia patients in South Korea. This descriptive research study was designed to identify the relationship between olfaction, depression, and each domain of cognitive function in elderly dementia patients. The participants of this study were 117 patients who visited the outpatient clinic between March and September 2019. More significant impairment of olfactory function was found in those with mild (7.48±1.28) or moderate (7.37±2.22) test scores of the Expanded Clinical Dementia Rating (CDR) scale than in those with questionable scores (20.58±6.18). The language domain of cognitive function, age, and education level showed 39.8% explanatory power for olfactory function (F=24.593, p<.001). It is expected that assessment of olfactory function in elderly people can lead to the early detection, diagnosis, and treatment dementia. Furthermore, it is important for future studies to confirm the relationship between each domain of cognitive function and olfactory function according to the type of dementia and to establish criteria for screening dementia in order to utilize olfactory function as a clinical marker.